2015
DOI: 10.1002/adom.201500378
|View full text |Cite
|
Sign up to set email alerts
|

Large Transmittance Change Induced by Exciton Accumulation under Weak Continuous Photoexcitation

Abstract: optical modulation over large areas, these changes are potentially suitable for applications such as real-time holograms, [ 6 ] light-beam modulation for continuouswave lasers, and security media.Another possible approach to achieve large optical modulations under weak incoherent photoexcitation is through the accumulation of triplet excitons in materials, which can infl uence various physical properties such as absorption, [ 10 ] refractive index, [ 11 ] and magnetic properties. [ 12 ] Unlike the short li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The large broadening is related largely to a saturation of p RTP intensity, which depends on excitation intensity. It has been reported that saturation occurs because of annihilation that is caused mainly by a singlet–triplet resonance energy transfer and a triplet–triplet resonance energy transfer because of a concentrated accumulation of triplet excitons in the materials. , In epifluorescent imaging with a resolution that approaches the diffraction limit, the excitation profile of the line width does not have a top-hat shape. Therefore, the emission profile has a center ((i) in Figure d) and tail parts ((ii) in Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…The large broadening is related largely to a saturation of p RTP intensity, which depends on excitation intensity. It has been reported that saturation occurs because of annihilation that is caused mainly by a singlet–triplet resonance energy transfer and a triplet–triplet resonance energy transfer because of a concentrated accumulation of triplet excitons in the materials. , In epifluorescent imaging with a resolution that approaches the diffraction limit, the excitation profile of the line width does not have a top-hat shape. Therefore, the emission profile has a center ((i) in Figure d) and tail parts ((ii) in Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Φ p (RT) of the C(C 6 H 5 ) 4 , Si(C 6 H 5 ) 4 , and Ge(C 6 H 5 ) 4 crystals in air were 3.1%, 5.1%, and 17%, respectively. We carefully measured Φ p (RT) and τ p (RT) because triplet accumulation by strong excitation intensity triggers fluorescence resonance energy transfer from S 1 to accumulated triplet excitons, phosphorescence resonance energy transfer from T 1 to accumulated triplet excitons, and triplet–triplet annihilation, which cause underestimation of Φ p (RT) and τ p (RT) . We confirmed that underestimation did not occur when 280 nm excitation light with a power of 1.0 mW cm −2 was used because linear increases of fluorescence and RTP were observed around this excitation intensity (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In materials with persistent RTP, the intensity of phosphorescence (the population of triplet states) gradually saturates as the excitation intensity increases . In the case of the CzDClT single crystal, intensity saturation of persistent RTP was observed when excitation intensity was above 0.01 mW cm −2 (Figure S6a, Supporting Information).…”
Section: Calculated Parameters Of Transfer Integral Reorganization Ementioning
confidence: 98%